The final walk with preptin - Mrázková, Lucie; Lubos, Marta; Voldřich, Jan; Kužmová, Erika; Zrubecká, Denisa; Gwozdiaková, Petra; Buděšínský, Miloš; Asai, Seiya; Marek, Aleš; Pícha, Jan; Tencerová, Michaela; Ferenčáková, Michaela; et al. (PloS one, 2024)
Preptin, a 34-amino acid peptide derived from pro-IGF2, is believed to influence various physiological processes, including insulin secretion and the regulation of bone metabolism. Despite its recognized involvement, the precise physiological role of preptin remains enigmatic. To address this knowledge gap, we synthesized 16 analogs of preptin, spanning a spectrum from full-length forms to fragments, and conducted comprehensive comparative activity evaluations alongside native human, mouse and rat preptin. Our study aimed to elucidate the physiological role of preptin. Contrary to previous indications of broad biological activity, our thorough analyses across diverse cell types revealed no significant biological activity associated with preptin or its analogs. This suggests that the associations of preptin with various diseases or tissue-specific abundance fluctuations may be influenced by factors beyond preptin itself, such as higher levels of IGF2 or IGF2 proforms present in tissues. In conclusion, our findings challenge the conventional notion of preptin as an isolated biologically active molecule and underscore the complexity of its interactions within biological systems. Rather than acting independently, the observed effects of preptin may arise from experimental conditions, elevated preptin concentrations, or interactions with related molecules such as IGF2.
Keywords: peptidové fragmenty; Protein Precursors; Rats; inzulin; krysa rodu Rattus; Animals; Peptide Fragments; lidé; insulinu podobný růstový faktor II; myši; Humans; zvířata; Mice; Insulin-Like Growth Factor II; proteinové prekurzory; Insulin